Strategic Management Model of Organizational Citizenship Behavior in the Hospitality Industry Using Fuzzy AHP Analysis - Pratiwi, Ika; Yusnita, Nancy; Hamzah, Hamzah (Yayasan Riset dan Pengembangan Intelektual, 2024)
Human resources play an important role in the development of the hotel sector in Banten Province. So that good governance needs to be considered by all hotel management, especially for the management of star hotels which have experienced a decline in visitors over the past three years, one of which is the result of the low quality of human resources of hotel employees. For this reason, this research was conducted as a step to determine strategies to improve employee organizational citizenship behavior in the hospitality sector. Of the three alternative strategies tested using the AHP analysis method, among others, alternative strategy 1 is a policy to improve the positive work environment through recognition. Alternative strategy 2 is a policy to improve the positive work environment through recognition and alternative strategy 3 is a policy by giving full attention to employees and providing constructive feedback. The results showed that the alternative strategy with the highest priority scale to improve OCB is an open and sustainable communication policy strategy between leaders and employees. While the second priority scale is with the Policy strategy by giving full attention to employees and providing constructive feedback. While the last priority scale is with a policy strategy to improve the positive work environment through recognition. Through increasing the sense of trust (trust) by paying attention to the indicator of trust in teamwork as the most dominant indicator. This can be improved through increasing group competence in the common goals of the organization. Increase open, honest communication between employees, and create a work atmosphere that can support collaboration among employees.